In Search of the Subaltern in Comparative Literature - Amirhossein Vafa (مطالعات بین‌رشته‌ای ادبیات، هنر و علوم انسانی)
In this article, by way of reviewing Gayatri Chakravorty Spivak’s views on “Subaltern Studies,” we will study her recent work in Comparative Literature. Spivak, who has constantly positioned herself against the elitist structure and discourse of the humanities in both Western and developing societies, believes that the comparative study of world literature, which today is in tandem with the capitalist logic of globalization, requires a methodological reorganization beyond the Eurocentric history of the discipline, as well as a turn to language learning from subaltern communities, including the refugees, the labour migrants, and other victims of the history of imperialism and global capitalism. In the pages that follow, by reading a selection of Spivak’s work—“Can the Subaltern Speak?” (1985), Death of a Discipline (2003), and “Rethinking Comparativism” (2009)—we will answer this question: Will postcolonial literary traditions (such as Persian literature) have the opportunity to express themselves on the global stage from within the framework of Comparative Literature? Spivak’s response is “Yes,” subject to the growth of the critic’s awareness of the inequalities prevalent in the global literary system, and the deconstruction of literary studies towards a discipline which Spivak calls “new comparative literature”: a new paradigm that is based on “deep language learning,” and the analysis of the culture and literature of the “subaltern” peoples.